The "Classes on the net" research project: The involvement and opinion of parents - Pieri, Michelle; Mangione, Giuseppina Rita Jose (International Journal about Parents in Education, 2023)
This paper focuses on the involvement of parents in the “Classes on the net” research project and their opinion and suggestions about this project. “Classes on the net” is a hybrid model, based on the idea of working with classrooms as Knowledge Building Communities This educational model can improve the management of small and isolated classes characterized by multigrade classes. In “Classes on the net”, delocalized classes aim to design a common disciplinary path involving student groups in parallel in the same activities by adapting calendars, spaces, and teacher roles. Teachers of delocalized classes share cooperative educational practices such as “pairs aidants/peer supporters”, “mentorat/mentoring” or “delocalized equipe” by using Video conferencing and Knowledge Forum. “Classes on the net” model was tested for the first time in Italy in the Abruzzo small schools in the school year 2020/2021. The experimentation involved 12 small schools, 11 digital animators, 31 teachers, and 6 observers (school principals). This experimentation did not originate during COVID-19 to address the issues that the pandemic generated but was planned and started before the advent of emergency, obviously, the experimentation was influenced by COVID-19. The present paper, after the literature review concerning remoteness and parenting in small and rural schools and home- school partnership in rural educational settings, will introduce the “Classes on the net” model and present the focus group result held with parents. The focus group took into consideration parent-school relationship, parents and information and communication technology, and the involvement of parents in the research project and their opinion about it.